A new species of the genus Liotyphlops Peters, 1881 (Serpentes: Anomalepididae) from the Caribbean coast of Honduras - Antúnez-Fonseca, Cristopher A.; Ramos-Galdamez, Josue; Solís, José Mario; Diaz-Ricaurte, Juan C.; Wilson, Larry David (Zootaxa, 2024)
We describe a new species of the genus Liotyphlops from the Caribbean coast of Honduras in Nuclear Mesoamerica, a genus previously known only from Isthmian Mesoamerica and northern, central, and eastern South America. Our description is based on a single specimen found by chance. The new species differs from other congeners by unique combination of external morphological characteristics, specifically by the presence of three scales on the first vertical row of the dorsals, three supralabial scales, 425 dorsal scales, and dorsals in 22 series of uniformly pigmented scales across the body. The type locality represents the northernmost record for the genus and is located 920 km (airline) northwest of the previous record for Liotyphlops albirostris in Costa Rica. We developed an identification key for the genus and discussed natural history and biogeographical aspects of Liotyphlops, including the species described here.